O LÚDICO EM INSTITUIÇÕES DE EDUCAÇÃO NÃO-FORMAL: CENÁRIOS DE MÚLTIPLOS DESAFIOS, IMPASSES E CONTRADIÇÕES - Natali, Paula Marçal (2009)
This study has as aim to investigate the subjacent concepts to the speeches of the subjects involved in the process of the Non-Formal Education in the city of Maringa, having as the main spot ludic and sport activities. The main questions which guided this study consider reflections about the assistance directed to children and teenagers in a vulnerable situation in Maringá, the analysis of the configurations of the Non-Formal Education scenario in the Brazilian Education and the factors which define the educational practices in institutions in the Third Sector. It was analyzed two philanthropic and social institutions in Maringa. The study is characterized by being a qualitative and multi-referential. The theoretical reference is composed by authors of the Popular Education, Non-Formal Education and critics of the Third Sector. The methodological procedures applied were: semi-structured interviews and focal groups. In order to understand the policy considering the assistance to children and teenagers interviews were performed with the members of the Municipal Committee of Children and Teenagers Rights – MCCTR and with employees of the Secretariat of Social Assistance and Citizenship – SSAC. To understand the effectiveness of these policy and the educational practices of the institutions, it was performed interviews with the social tutors, coordinators of the supplementary activities outside class time and also the assembling of focal groups with teenagers from the institutions. The main considerations about this study are: the SSAC establishes, most of the times, a relation with the institutions of supplementary activities outside class time of the bureaucratic and distant city. The MCCTR is characterized as a structure that seeks the democratic acting, but ends up being limited to projects, reports, few visits and verifies the denunciations. In relation to the social educators it is understood that they need to build up the educative action as a group, to reflect about the performed studies and reflect in order to discuss the aims and projects of the institutions of supplementary activities outside class time in which they work, to mediate the institutional proposals of the popular classes and the social policy. In relation to the teenagers, it is verified that they are from popular classes with a very low scholar output and who consider the institutions of supplementary activities outside class time that they participate a cozy space and an opportunity of being inserted into the work market and the ludic and sport activities represent a leisure and compensating time due to the routine that they have. In this way it was possible to highlight the urgent necessity of reflections about the public policy and educative actions formed in the partnerships established with the Third Sector and the State in order to the social inclusion of the children and teenagers in a vulnerable situation.